A SYSTEMATIC APPROACH TO THE ORGANIZATION OF EDUCATIONAL PROCESSES IN GENERAL SECONDARY EDUCATION INSTITUTIONS - Ismoilova Gulbaxor Azamovna,; Kazimova Xilolakhon Mansurkhon qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article scientifically substantiates the systematic approach to the organization of teaching and educational processes in general secondary education institutions.